Recent Developments of Gramine: Chemistry and Biological Activity - Jiaoyue Zhang; Qitao Jia; Na Li; Liqiang Gu; Wenjia Dan; Jiangkun Dai (Molecules, 2023)
The natural alkaloid gramine has attracted significant attention in both academic and industrial circles because of its potential and diverse biological activities, including antiviral, antibacterial, antifungal, anti-inflammatory and antitumor activities; application in therapy for Alzheimer’s disease; serotonin-receptor-related activity; insecticidal activity; and application as an algicide. In this review, we focus on the research advances that have been made for gramine-based molecules since their discovery, providing key information on their extraction and separation, chemical synthesis and diverse biological activities. Data regarding their mechanisms of action are also presented. This comprehensive and critical review will serve as a guide for developing more drug candidates based on gramine skeletons.